Assessing the effect of insecticide-treated cattle on tsetse abundance and trypanosome transmission at the wildlife-livestock interface in Serengeti, Tanzania. - Jennifer S Lord; Rachel S Lea; Fiona K Allan; Mechtilda Byamungu; David R Hall; Jessica Lingley; Furaha Mramba; Edith Paxton; Glyn A Vale; John W Hargrove; Liam J Morrison; Stephen J Torr; et al. (Public Library of Science (PLoS), 2020)
In the absence of national control programmes against Rhodesian human African trypanosomiasis, farmer-led treatment of cattle with pyrethroid-based insecticides may be an effective strategy for foci at the edges of wildlife areas, but there is limited evidence to support this. We combined data on insecticide use by farmers, tsetse abundance and trypanosome prevalence, with mathematical models, to quantify the likely impact of insecticide-treated cattle. Sixteen percent of farmers reported treating cattle with a pyrethroid, and chemical analysis indicated 18% of individual cattle had been treated, in the previous week. Treatment of cattle was estimated to increase daily mortality of tsetse by 5-14%. Trypanosome prevalence in tsetse, predominantly from wildlife areas, was 1.25% for T. brucei s.l. and 0.03% for T. b. rhodesiense. For 750 cattle sampled from 48 herds, 2.3% were PCR positive for T. brucei s.l. and none for T. b. rhodesiense. Using mathematical models, we estimated there was 8-29% increase in mortality of tsetse in farming areas and this increase can explain the relatively low prevalence of T. brucei s.l. in cattle. Farmer-led treatment of cattle with pyrethroids is likely, in part, to be limiting the spill-over of human-infective trypanosomes from wildlife areas.